In Vitro and In Vivo Antifungal Activity of Amphotericin B Lipid Complex: Are Phospholipases Important? - Swenson, Christine E. (American Society for Microbiology, 1998)
Amphotericin B lipid complex for injection (ABLC) is a suspension of amphotericin B complexed with the lipids l-α-dimyristoylphosphatidylcholine (DMPC) and l-α-dimyristoylphosphatidylglycerol. ABLC is less toxic than amphotericin B deoxycholate (AmB-d), while it maintains the antifungal activity of AmB-d. Active amphotericin B can be released from ABLC by exogenously added (snake venom, bacteria, or Candida-derived) phospholipases or by phospholipases derived from activated mammalian vascular tissue (rat arteries). Such extracellular phospholipases are capable of hydrolyzing the major lipid in ABLC. Mutants of C. albicans that were resistant to ABLC but not AmB-d in vitro were deficient in extracellular phospholipase activity, as measured on egg yolk agar or as measured by their ability to hydrolyze DMPC in ABLC. ABLC was nevertheless effective in the treatment of experimental murine infections produced by these mutants. Isolates of Aspergillus species, apparently resistant to ABLC in vitro (but susceptible to AmB-d), were also susceptible to ABLC in vivo. We suggest that routine in vitro susceptibility tests with ABLC itself as the test material may not accurately predict the in vivo activity of ABLC and that the enhanced therapeutic index of ABLC relative to that of AmB-d in vivo may be due, in part, to the selective release of active amphotericin B from the complex at sites of fungal infection through the action of fungal or host cell-derived phospholipases.